Structural, spectroscopic and DFT study of 4-methoxybenzohydrazide Schiff bases. A new series of polyfunctional ligands - Ferraresi Curotto, Verónica (2015)
Five Schiff bases obtained from condensation of 4-methoxybenzohydrazide with related aldehydes, namely o-vanillin, vanillin, 5-bromovanillin, 5-chlorosalicylaldehyde and 5-bromosalicylaldehyde were prepared. A detailed structural and spectroscopic study is reported. The crystal structures of four members of the family were determined and compared with one another. The hydrazones obtained from 5-chlorosalicylaldehyde and 5-bromosalicylaldehyde resulted to be isomorphic to each other. The solid-state structures are stabilized by intra-molecular OH⋯N interactions in salicylaldehyde derivatives between the OH moiety from the aldehyde and the hydrazone nitrogen atom. All crystals are further stabilized by inter-molecular H-bonds mediated by the crystallization water molecule. A comparative analysis between experimental and theoretical results is presented. The conformational space was searched and geometries were optimized both in gas phase and including solvent effects. The structure is predicted for the compound for which the crystal structure was not determined. Infrared and electronic spectra were measured and assigned with the help of data obtained from computational methods based on the Density Functional Theory.